THE UNITED STATES FOREIGN POLICY AGAINST AFGHANISTAN MILITARY: A COVERT MILITARY METHOD - Akaber Jhosep (Jurnal Pembaharuan Hukum, 2022)
This study aims to analyze and explain the foreign policy of the United States towards the Afghan militia, especially the Taliban. The United States government with the help of the CIA (Central Intelligence Agency) investigates and seeks to destroy the Al Qaeda terrorist group led by Osama bin Laden who was later found to be in Afghanistan and obtained protection under the Taliban. The Taliban, the Islamic extremist regime that controls Afghanistan and offers space for Al Qaeda militants to exercise its military in Afghanistan. President Bush signed a resolution on September 18, 2001 regarding the attacks on Al Qaeda under the protection of the Taliban in Afghanistan which continues to this day. The United States is actively involved in supporting military operations in Afghanistan, including logistical assistance, Afghan military training, and sending American military troops to conflict areas. The main goal of the United States in doing so is to prevent potential future attacks by a growing terrorist group in Afghanistan. Based on data from the United States Department of Defense, the total expenditure in the military sector in Afghanistan from 2001 to 2019 was 778 billion USD. Meanwhile, the number of troops sent to conflict locations was 596,303 troops. There are 2,441 US military troops confirmed dead in the Afghan war from 2001 to 2019. It is estimated that about 12,000 US military troops are still in Afghanistan. This research is a qualitative research and the data collection technique used by the author in this study is Library Research in the form of books, journals, documents, reports, articles, or newspapers obtained through electronic and non-electronic media. The conclusion is that this foreign policy is relevant and elaborates that in international relations there will be actions, reactions, and interactions between political entities called states. The state, in this case the head of state as the decision maker, tries to formulate every goal to be achieved by minimizing sacrifices to the national interest. In line with the policies pursued by President Trump to end the war in Afghanistan and withdraw all military forces of the United States and its allies.